Evaluasi Kebijakan Penerapan Aplikasi E-Commerce (Aplikasi Bebaya Mart di Kota Samarinda) - Perwitasari , Dyah Rahayuning; Rizal, Muhammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
This research aims to present an evaluation of the policy for implementing e-commerce applications (the Bebaya Mart application in Samarinda City) and determine the impact of this policy. This research focuses on policy evaluation through the approaches of effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. This type of research is descriptive qualitative with purposive sampling and snowball sampling techniques. The primary data used in this research is data from interviews with Perumda Varia Niaga Samarinda City and supported by secondary data. The research was carried out at Perumda Varia Niaga Samarinda where the research results showed that this policy had been implemented well in terms of efficiency, responsiveness, alignment and accuracy. However, if we look at the effectiveness and adequacy of this policy, it is still not implemented well because people prefer conventional shopping rather than online shopping through the Bebaya Mart application.